Quality as Ideology: Criticism of Instrumental Rationality in Internal Quality Assurance at School - Moh. Imam Wahyudi; Siti Aimah (Journal of Educational Management Research, 2026)
This study aims to examine internal quality assurance as an ideology constructed through instrumental rationality and to analyze its implications for educational management, pedagogical practices, and student learning experiences. Employing a qualitative approach within an interpretive paradigm, this study explores how quality assurance is socially constructed and enacted in school management. Data were collected through in-depth interviews with school leaders, teachers, and administrative staff, participatory observations, and document analysis. The data were analyzed thematically to identify patterns related to managerial rationality, quality discourse, and pedagogical consequences. Trustworthiness was ensured through source and method triangulation, informant verification, and contextual interpretation. The findings reveal that internal quality assurance is predominantly framed as an administrative and symbolic mechanism to achieve institutional legitimacy. Quality management practices emphasize documentation, reporting, and quantitative indicators, while pedagogical depth and student learning experiences receive less attention. This technocratic orientation constrains teacher autonomy, limits pedagogical innovation, and creates tensions between managerial accountability and instructional responsiveness. The study highlights the need to reform quality assurance systems in educational management by balancing administrative compliance with pedagogical development, empowering teachers, and repositioning student learning experiences as the core objective of quality improvement.